2017
DOI: 10.17549/gbfr.2017.22.4.65
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a CEO’s Technical Background and Cross-functional Coordination on Technological Innovation Performance: The Mediating Role of Technological Innovation Orientation

Abstract: A B S T R A C TThe major purpose of this research is to provide a refined understanding of the effects of a CEO's technically oriented functional background and cross-functional coordination on the firm's technological innovation performance by including as a mediating variable in the research model the construct of technological innovation orientation which has been recently identified as an important factor affecting the firm's technological innovation performance. Strategic management and innovation researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Choe (2016) observed that the competitive usage of knowledge asset had a positive impact on the performance of an organization. Moon (2017) confirmed in his study that a CEO's technically oriented functional background affected the firm's technological innovation performance.…”
Section: A Literature Reviewsmentioning
confidence: 79%
“…Choe (2016) observed that the competitive usage of knowledge asset had a positive impact on the performance of an organization. Moon (2017) confirmed in his study that a CEO's technically oriented functional background affected the firm's technological innovation performance.…”
Section: A Literature Reviewsmentioning
confidence: 79%
“…Internal factors include the CEO's willingness and corporate culture and external factors include external network. Moon (2017) confirmed in his study that the CEO's technically oriented functional background affects the firm's technological innovation performance.…”
Section: Influencing Factors In Previous Studiesmentioning
confidence: 79%
“…Especially, the CEO in high technology firms plays a more significant role in managing corporate decisions. 1) As high CEO equity incentive motivates a CEO to be more discretionary, this study anticipates that the CEO of a high technology 1) Moon (2017) finds that technical backgrounds of the CEO can affect on his or her technology-related decisions, indirectly contributing to positive firm performance.…”
Section: ⅰ Introductionmentioning
confidence: 94%